"Carrier–drug" layer-by-layer hybrid assembly of biocompatible polydopamine nanoparticles to amplify photo-chemotherapy. Issue 37 (13th September 2022) - Lv, Lingyu; Cheng, Hao; Wang, Zhen; Miao, Zhangyi; Zhang, Feng; Chen, Jie; Wang, Gang; Tao, Ling; Zhou, Jianping; Zhang, Huaqing; Ding, Yang
Abstract : "Carrier-drug" layer-by-layer hybrid assembly was developed by layer-by-layer co-assembly of DOX and dopamine with high drug loading, multiple-responsive drug release and deep tumor penetration to amplify chemo-photothermal anti-tumor therapy. Abstract : Polydopamine (PDA) is capable of wide drug delivery for biomedical applications by virtue of an adjustable polymerization process, including surface coating and conjugation. Inspired by the polymerization of dopamine, we introduce a layer-by-layer hybrid co-assembly strategy for the incorporation of doxorubicin (DOX) and dopamine to form PDA "carrier–drug" hybrid assembly. The "carrier–drug" hybrid assembly relies on the π–π stacking interaction between the drug (DOX) and carrier (PDA), and such the stacked-layer structure enables PDA nanoparticles with a superior drug loading of 58%, which is about 1.7-fold higher than that of the DOX surface coating (∼35%). To further improve blood circulation stability and enhance tumor penetration, we herein propose the conjugation of native apolipoprotein A-I (apoA-I) with tumor-homing cyclic peptide iRGD for PDA surface modification. The "carrier–drug" hybrid assembly can respond to triple stimuli of the acidic pH, concentrated reactive oxygen species (ROS), and near-infrared (NIR) light irradiation for realizing site-specific and on-demand drug release. In chemo-photothermal synergy therapy, the "carrier–drug" hybrid assembly performs efficient tumor penetration and accumulation, dramatically suppressing tumor growth and metastasis in a 4T1 orthotopic tumor-bearing mice model at a safe level. Collectively, our findings share new insights into the design of "carrier–drug" hybrid assembly for enhanced chemo-photothermal oncotherapy.